The Use of Mind Mapping on Tony Buzan’s Perspective in Learning Processes - Putri Rahayu, Arum (Jurnal Paradigma, 2021)
Mind Mapping is not a matter of life-death, success-failure, or a rigid mind. Through mind mapping, no one will be able to assess the individual's final result, because the mind mapping made by one individual will be different from another individual. Mind mapping is a technique or method to align the right brain and left brain in receiving new information. Mind mapping is the most creative and effective way to take notes, through the use of mind mapping, it is hoped that students will be more creative, confident, and able to master lessons more quickly.